Childhood trauma in children at familial high risk of schizophrenia or bipolar disorder: A longitudinal study. The Danish High Risk and Resilience Study – VIA 7 and VIA 11. (24th March 2022) - Brandt, Julie Marie; Hemager, Nicoline; Gregersen, Maja; Søndergaard, Anne; Falkenberg Krantz, Mette; Ohland, Jessica; Wilms, Martin; Birkehøj Rohd, Sinnika; Hjorthøj, Carsten; Veddum, Lotte; Bruun Knudsen, Christina; Krogh Andreassen, Anna; et al.
Abstract: Objectives: Childhood trauma increases the risk of developing mental illness as does being born to parents with schizophrenia or bipolar disorder. We aimed to compare prevalence of lifetime childhood trauma among 11‐year‐old children at familial high risk of schizophrenia (FHR‐SZ) or bipolar disorder (FHR‐BP) compared with population‐based controls (PBCs). Design: The study is a longitudinal, prospective cohort study of children at FHR‐SZ, FHR‐BP, and PBCs. Methods: A cohort of 512 children at FHR‐SZ ( N  = 199), FHR‐BP ( N  = 118), and PBCs ( N  = 195) were examined at baseline (mean age 7.8, SD 0.2) and 451 children at FHR‐SZ ( N  = 172), FHR‐BP ( N  = 104), and PBCs ( N  = 175) were examined at four‐year follow‐up (mean age 11.9, SD 0.2, retention rate 87.3%). Childhood trauma was measured with a semi‐structured interview. Results: Children at FHR‐BP had an elevated risk of exposure to any lifetime trauma (age 0–11 years) compared with PBCs (OR 2.082, 95%CI 1.223–3.545, p  = .007) measured with binary logistic regression. One‐way ANOVA revealed that both FHR‐groups had a higher lifetime prevalence of exposure to a greater number of types of trauma compared with PBCs (FHR‐SZ: observed mean: 1.53, 95%CI 1.29–1.77; FHR‐BP: observed mean: 1.56, 95%CI 1.26–1.85; PBCs: observed mean: 0.99, 95%CI 0.82–1.17; p  < .001). Binary logistic regression showed that the lifetime risk of exposure to interpersonal trauma (age 0–11 years) was elevated for both FHR‐groups (FHR‐SZ: OR 3.773, 95%CI 2.122–6.710, p  < .001; FHR‐BP: OR 3.602, 95%CI 1.913–6.783, p  < .001). Conclusions: Children at FHR‐SZ and FHR‐BP are at increased risk for being exposed to childhood trauma compared with PBCs. This study underscores the need for early detection, support, and prevention of childhood trauma in children at FHR‐SZ and FHR‐BP.